Ubuntu Philosophy for the New Normalcy - Siraz Chowdhury, Jahid; Wahab, Haris Abd.; Mohd Saad, Mohd Rashid; Mathbor, Golam M.; Hamidi, Mashitah (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
The book is about Ubuntu-loosely translated-I am because we are-or, our common humanity in Zulu, about Unity, and global solidarity. It proves again how alike and universal we are as societies across the globe despite this deadly pandemic. On a personal and social basis, each of the six chapters is a call to action to find commonality, and this is the third book of Jahid's amelioration on Covid-19 Trilogy. And the Appendix is something special for the readership. Ubuntu tells us about the Indigenous healing keys: empathy, compromise, learning, non-violence, change, forgiveness, restorative justice, love, spirituality and hope. The book was written by a highly diverse team of contributors, both from the Global South and North, and is multidisciplinary in nature, and attempting of Commoning the Communities. The authors hail from the fields of social work, anthropology, and education, and have been working with local communities in the ongoing struggle to identify and address complicit oppression and inequalities. Offering a beacon of hope for today and tomorrow, the book will appeal to social science researchers, policy planners, and the general public alike. Jahid Siraz Chowdhury is PhD candidate from the Universiti Malaya, Malaysia. A creative writer, he has published 13 books in Bengali, including "'Purbo-Prantic' Eastern Corner," a historical novel tracing back from 600 to 1304 AD in the eastern part of Bangladesh. He is currently working for Selfosophy and Reciprocity in Social Research. His intended areas are Philosophy of Knowledge, Research Methodology and Bioprospecting. Haris Abd Wahab is a Professor at the Department of Social Administration and Justice, and Deputy of Dean (Student Affairs), Universiti Malaya, Malaysia. His core area of expertise is Community Development, street children. Mohd Rashid Mohd Saad is a Senior Lecturer at the Department of Education at the Universiti Malaya, Malaysia. His core area of expertise is inclusion of Indigenous Knowledge into drug discovery. Golam M. Mathbor is a Professor in the School of Social Work, Monmouth University, USA. He has been working with marginalized people. Mashitah Hamidi is a Senior Lecturer in Social Work at the Department of Administration and Social Justice, Universiti Malaya, Malaysia. She has been working with marginalised groups focusing on lab or and gendered migration, stateless people and refugees.
Introduction: We Are Weing -- Research is not Greater than the Methodology -- What does Ubuntu Manifest in This Pandemic -- Why Ubuntu can be -- And How -- Concluding reflection: Seeing self through other.
Keywords: Africa -- Religion; Philosophy; Anthropology; African Religions; Philosophy; Anthropology